The effect of bleeching technic and storage temperature on the quality of (Lactuca sativa L) during storage - Rosdiana, Rosdiana; Agusta, Waqif; Kurniawan, Endang (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
The purpose of this study was to determine the effect of the lettuce washing technique with water and dish soap, the storage temperature, and the combination of the two treatments on the quality of the lettuce. This research was conducted in June - August 2020 at Puspiptek Serpong, South Tangerang. The experimental design used was a two-factorial completely randomized design and three replications. The first factor is the technique of washing with water, control and dish soap; the second factor is the temperature of 50C and 250C. Data analysis used F and BNJ test at 5% level. The variables observed were weight loss, color, water content, total sugar content, and respiration rate of O2. The results show that different washing techniques only affect the variables of weight loss and sugar content. The storage process with a temperature of 50C can maintain the quality of lettuce for five days of storage. The combination of dishwashing treatment with dish soap and a storage temperature of 50C gave better results than other combinations.